Применение автоматизированных имитационноизмерительных комплексов для оценки характеристик излучающих систем - Усин, В. А.; Марков, В. И.; Помазанов, С. В.; Усина, А. В.; Филоненко, А. Б. (ХНУРЭ, 2008)
Special automated complexes which allow integrating the processes of modeling, designing and measurements of the phased-array antenna (PAA) parameters for aligning, conducting acceptance tests, field trials and field calibration are considered in this report. It is shown that for comprehensive evaluation of multifunction PAA parameters it is necessary to combine procedures of simulation, diagnostics, factory alignment and field calibration of multi channel PAA, taking into account its constructive peculiarities and restrictions. Such approach optimizes and improves engineering decisions for perspective antennas by multivariant choice of its construction, measurement and monitoring methods while reducing time and costs of their development and implementation.
Keywords: излучающая система